Empowerment of Santri in Efforts to Prevent Daily Emergency at Sidogiri Islamic Boarding School, Pasuruan, East Java - Loetfia Dwi Rahariyani; Kusmini Suprihatin; Dony Sulystiono; Alfi Maziyah (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2022)
The number of Islamic boarding schools is increasing rapidly, leading to potential health problems, particularly emergency-related issues. This community service aims to improve the students’ health by preventing daily emergencies through the formation of a Healthy Santri Cadre. The benefits of this activity include improving the students’ health and preventing daily emergencies in the Islamic boarding school environment. This community service activity was held in collaboration with LAZ-Sidogiri during the COVID-19 pandemic, when the Sidogiri Islamic boarding school was in lockdown. The activity was divided into three stages: assessment, training of healthy santri cadres, and peer group training through healthy santri cadres. LAZ-Sidogiri staff trained 30 healthy santri cadres. The results of the study showed that all students had experienced emergency situations, with the most common being fever, falls, and cuts from sharp objects. The level of knowledge of the Healthy Santri Cadre before and after the training was statistically significant (p<0.05). The establishment of a Healthy Santri Cadre is essential in Islamic boarding schools as a means of preventing daily emergencies and increasing students’ ability to provide correct first aid.